Induction Chemotherapy Followed by Chemoradiotherapy With or Without Consolidation Chemotherapy Versus Chemoradiotherapy Followed by Consolidation Chemotherapy for Esophageal Squamous Cell Carcinoma - Xiang, Mingyue; Liu, Bo; Zhang, Guifang; Gong, Heyi; Han, Dali; Ma, Changsheng (Frontiers in Oncology, 2022)
Objective: To compare the efficacy and safety of induction chemotherapy followed by concurrent chemoradiotherapy(I-CCRT), induction chemotherapy followed by concurrent chemoradiotherapy and consolidation chemotherapy(I-CCRT-C), and concurrent chemoradiotherapy followed by consolidation chemotherapy(CCRT-C) for locally advanced esophageal squamous cell carcinoma(ESSC). Patients and Methods: Patients with locally advanced ESCC who underwent definitive chemoradiotherapy with cisplatin plus fluorouracil or docetaxel from February 2012 to December 2018 were retrospectively reviewed. Kaplan-Meier curve was used to estimate survival. Efficacy was assessed using RECIST, version 1.0. Prognosis factors were identified with Cox regression analysis. Results: Patients were treated with CCRT-C(n=59), I-CCRT(n=20), and I-CCRT-C(n=48). The median follow-up duration was 73.9 months for the entire cohort. The ORR of the CCRT-C, I-CCRT, and I-CCRT-C, SCRT groups was 89.8%, 70.0%, and 77.1%, respectively (P = 0.078). The median PFS in the CCRT-C, I-CCRT, and I-CCRT-C groups was 32.5, 16.1, and 27.1 months, respectively (P = 0.464). The median OS of the CCRT-C, I-CCRT, and I-CCRT-C groups was 45.9, 35.5, and 54.0 months, respectively (P = 0.788). Cox regression analysis indicated that I-CCRT-C and I-CCRT did not significantly prolong PFS and OS compared with CCRT-C(P > 0.05). Neutropenia grade ≥ 3 in CCRT-C, I-CCRT, and I-CCRT-C groups was 47.5%, 15%, and 33.3% of patients, respectively(P=0.027). Conclusions: I-CCRT and I-CCRT-C using cisplatin plus fluorouracil or docetaxel regimen are not superior to CCRT-C in survival, but seem to have less severe neutropenia than CCRT-C. Further randomized controlled studies are warranted.